Informing the Development of Domestic Energy Efficiency Initiatives: An Everyday Householder-Centered Framework - Parnell, Rosie; Larsen, Olga Popovic (Environment and behavior, 2005)
This article challenges the assumptions of the techno-economic paradigm that has dominated U.K. energy policy and associated domestic energy efficiency programs since the 1970s. The process of development of an alternative conceptual framework, the everyday householder-centered approach, is described. The study began with semistructured interviews with domestic energy efficiency program providers, the results of which guided a subsequent literature review. The developed framework was structured around three core traits of the everyday householder in the context of information and advice programs for domestic energy efficiency: self-interest, energy knowledge, and cognitive capacity. The conceptual framework is presented for practical application in guiding the development of effective information and advice-focused domestic energy efficiency programs.